PROTOTIPE MONITORING KETINGGIAN AIR DAN KONTROL JARAK JAUH PINTU AIR PADA BENDUNGAN - Ramadhani, Tarisa Auliya; Gunawan, Putri Miya; Fitriani, Lely Mustikasari Mahardhika; Yusuf, Arief Rahman (Jurnal Ilmiah Teknologi dan Rekayasa, 2024)
In an effort to enhance the efficiency and accuracy of dam monitoring, there is a need for more advanced systems compared to the manual methods still widely used. This study aims to design and develop a prototype system for monitoring water levels and controlling dam gates that can be operated automatically and in real-time. The methods used include ultrasonic sensors and water level float switches connected to an ESP-8266 microcontroller, as well as DC motors and relays to operate the dam gates. The data collected by the sensors is transmitted via the internet for remote monitoring. The results of the study show that the developed system can monitor water levels with 96% accuracy and 4% error, and provides a quick response to changes in water conditions. This system can also send real-time notifications through a web application, helping to reduce human workload and increase community preparedness around the dam area for potential flooding.